Inequality causes and consequences Research in labor economics - Polachek, Solomon W.; Tatsiramos, Konstantinos; Cappellari, Lorenzo (UK Emerald Group of Publishing, 2016)
Inequality of opportunity in Europe:Is there a role for institutions?